COMPOSITION OF SURROUNDING NET CATCHES IN VILLAGE OF PASAR II WATERS, MANDAILING NATAL DISTRICT, NORTH SUMATERA PROVINCE - Ali Basri Rangkuti; Arthur Brown; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis research was conducted in September 2019 for 1 week in the waters of Pasar II Natal Village, Natal District, Mandailing Natal Regency, North Sumatra Province. The purpose of this study is to produce  data information about the composition of the basic lampara which is operated in the waters of the Pasar II Natal District of Natal District of Mandailing Natal. The method used in this study is a survey method, data obtained by fishing experiment using surrounding net which is operated by fishermen in the District of Natal Mandailing Natal seawaters, North Sumatra Province. The catch fishes are raised by fishermen ashore using a 30 kg basket. While the catch fish obtained during the research activities consists of red Lutjanus bitaeniatus, Doryteuthis pealeii, Rastrelliger faughni, Trichiurus lepturus, Eubleekeria splendens, Sardinella albella and Stolephorus indicus. Total catches obtained were 1876 kg with 819873 individuals. Actually,the target fish    Anchovies (Stolephorus indicus)  was caught with a total weight of 1696 kg with a percentage of 90.40% of the total weight of the catch fish. The number of anchovies obtained is 814080 or 99.29% of the total catch. The bycatch of fish obtained weighing 180 kg or as many as 5793 fishes. Keywords: Basic Attachment, Stolephorus indicus, Primary and Secondary